A High-Precision Curvature Compensation Reference Circuit for a Cable Accessory Image Acquisition Device - Ning Xiao; Yuewei Tian; Xiaosong Peng; Weijun Wang; Wenqiang Zou; Chao Yuan; Qian Zhou (Energies, 2024)
High-voltage cables are widely used in power transmission and distribution systems, and their accessories (such as connectors, terminals, and insulators) are key parts to ensure the safe and reliable operation of power systems. These accessories may be affected by factors such as temperature, humidity, and mechanical stress during long-term operation, resulting in performance degradation or failure. In high-voltage environments, performance monitoring of cable accessories is crucial. The reference voltage circuit can withstand the influence of temperature changes and power supply fluctuations, support accurate current and voltage measurement, and thus detect potential faults in time to ensure the safe and stable operation of the power system. However, the traditional reference voltage circuit has a low-temperature curvature loss, which results in an inaccurate reference voltage, resulting in equipment damage. Therefore, in order to solve the problem of curvature loss in this part, this paper proposes a curvature compensation circuit, which realizes a high-precision reference voltage circuit through a high-temperature curvature compensation circuit, thereby meeting the current reference voltage requirements for cable accessory monitoring.